Consequências de situações meteorológicas anormais : breve reflexão - Pedrosa, António de Sousa (1991)
The heavy thunderstorm which took place in the region of Marao, in a place called Cumieira, in August 1989, had some significant geomorphological consequences. There were two main types of effects: on the one hand, the almost total destruction of the cultures which brought about severe financial losses for the farmers of the region; on the other hand, the movement along the slopes of great quantities of heterometrical materials, constituted by blocks of different sizes, some of them even of considerable dimensions. In this article the author tries to analyse some of the consequences of this abnormal meteorological condition on the environmental dynamics.